Prospects for “Book Culture" in the Context of Education Mediation - K. G. Antonian; N. A. Sokolova (Дискурс, 2020)
Introduction. In the modern era of media development, the social and cultural status of the book is inevitably rethought. The dominant means of transmitting and preserving information in culture as a whole, as well as in the educational system, today are digital devices, which, it would seem, are completely capable of replacing a book. The study aims to problematize the very concept of "book culture", as well as to identify the relevance of book culture in the context of the medial turn of the last third of the XX - beginning of the XXI centuries, in particular in the education system.Methodology and sources. Methodologically, the work is based on a cultural philosophical analysis of research literature.Results and discussion. The phenomenon of "book culture" is considered, transforming under the influence of new digital technologies and digital devices. The situation is analyzed when a generation of teachers of book culture and book-like thinking is faced with the need to master digital technologies and learn in a digital environment at a time when the generation of digital native comes to schools and universities, for which digital culture is not a subject of learning, but the natural habitat from birth.Book culture, like media culture or oral tradition, forms a certain type of perception of the world, sets the logic of thinking, which is especially important in the pedagogical process, when the skills of meaningful thoughtful work with text are formed. With the book, the reader enters into a dialogical relationship, it is individualized, which cannot be said about digital devices that are perceived and used to a greater extent exclusively functionally. Filling the pedagogical process with digital devices and visual information does not still exclude the enormous importance of the teacher's personality, but requires observation and reflection in order to understand the consequences (pluses and minuses) of such mediation.Conclusion. It can be assumed that the book will remain the main form of knowledge representation and the foundation of the educational process. However, book culture, as an integral and valuable attitude to the world, is inferior to the primacy of media culture, which should entail the adjustment of teaching methods and techniques, as well as the refinement of educational goals.